Cross-equatorial flow over southeast Asia during the Northeast monsoon - LIM , JOO TICK; QUAH, LEONG CHUAN (MAUSAM, 1978)
Computations of equatorial trajectories involving the voritcity equation as suggested by Fujita et at. (1969) were performed. Comparison of the trajectories for the early and late northeast monsoon months reveals that substantial cross-equatorial flow during the late monsoon period is the result of changes that take place in the Asia monsoon circulation. The causes of the cross-equatoial flow during the late monsoon period is the result of changes that take place in the Asia monsoon circulation. The causes of the cross-equatorial drift flow are also attributed to these changes with a further requirement of the strengthening of the winds over Southeast Asia especially over area north of latitude 100 N.